PROBLEMATIKA PEMUDA ISLAM: KAJIAN STRATEGIS DAKWAH YANG EFEKTIF - Deni Rahman; Daud Rasyid; Imam Santoso; Yusnita Yusfik; Wawan Hermawansyah; Syifa Nurlatifah (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi Islam Institut Agama Islam (IAI) Al-Azhaar Lubuklinggau, 2025)
This article aims to examine the potential, issues, and strategic role of young Muslims in preaching, both as subjects and objects. Youth have a central position as agents of social and spiritual change, but they also face internal issues such as a crisis of Islamic identity and a lack of religious understanding, as well as external issues such as the influence of globalization, social media, and economic challenges. The methodology used is literature study with a qualitative approach. Data is obtained through analysis of relevant literature, including the Qur'an, hadith, academic books, and journal articles. This approach aims to deeply explore the potential of young people, identify the issues they face, and formulate practical preaching-based solutions. Findings show that youth have the ability to utilize digital media, art, and popular culture as effective preaching tools. As objects of preaching, they require relevant, dynamic, and dialogue-based approaches to strengthen faith and religious understanding. Synergy between family, educational institutions, scholars, and the community is essential to support the holistic development of young people. Innovative and contextual preaching is expected to strengthen the Islamic identity of youth while also addressing the challenges of modern times. With the right approach, young Muslims can be empowered to become a generation of faith, morality, and positive contribution to society.